Democracy and Power The Delhi Lectures - Chomsky, Noam (Open Book Publishers, 2014)
"Noam Chomsky visited India in 1996 and 2001 and spoke on a wide range of subjects, from democracy and corporate propaganda to the nature of the world order and the role of intellectuals in society. He captivated audiences with his lucid challenge of dominant political analyses, the engaging style of his talks, and his commitment to social equality as well as individual freedom. Chomsky's early insights into the workings of power in the modern world remain timely and compelling. Published for the first time, this series of lectures also provides the reader with an invaluable introduction to the essential ideas of one of the leading thinkers of our time."